Kartun Nussa sebagai Media Pendidikan Karakter: Analisis Semiotik dalam Konteks Budaya Indonesia - Maulana, Alvin; Sa’adah, Arifatus; Fajriyah, Sari Ulfa; Mas’odi, Mas’odi (Universitas Pahlawan Tuanku Tambusai, 2025)
Nussa Cartoon is a local animation that combines the educational values of Islamic characters and Indonesian culture. Using Roland Barthes’ semiotic approach, this research aims to analyze there presentation of character education values in Nussa. This approach dissects denotative, connotative and mythical meanings. Data was obtained by analyzing several popular Nussa episodes, with emphasison visual elements, dialogue and symbols. The research results show that Nussa always shows valuessuch as religiosity, honesty, responsibility, cooperation and respect for parents. These values are interpreted according to Indonesian culture. This cartoon functions as a relevant informal educational medium to shape children’s character in the digital era and streng then local cultural identity. According to this research, local media is very important for conveying moral messages and supporting contextual character education. In this research, local media is very important for conveying moral messages and supporting character education that is contextual to community culture.